Analisis Pengaruh Pengawasan Fungsional, Akuntabilitas Publik Dan Peningkatan Pelayanan Publik Terhadap Kinerja Pemerintah Daerah (Studi Empiris Pada SKPD di Provinsi Jambi) - Wirmie Eka Putra (ITB AAS INDONESIA, 2018)
This study aims to determine whether Functional Control, Public Accountability and Improvement of Public Service affect the performance of Jambi Provincial Government simultaneously and partially. This research was conducted in the province of Jambi sourced from all SKPD Jambi Province. Number of SKPD analyzed a total of 32 SKPD that the Department and the Agency with a total population of 598, after using Taro Yamane formula for determining the number of samples of the total population and it can be the result of 86 respondents to be studied. The type of data used are primary data. Data obtained from questionnaires research on each SKPD province of Jambi. Testing the hypothesis in this study using multiple linear regression and testing using SPSS. Results from this study showed that simultaneous variables Functional Monitoring, Public Accountability and improvement of public services affect the Local Government Performance variables. Functional Monitoring partially affect the local Government Performance and Accountability of Public partially affect the Performance of Local Government and Public Service partially affect the Local Government Performance.